Comparative study of disk diffusion and microdilution methods for evaluation of antifungal activity of natural compounds against medical yeasts Candida spp and Cryptococcus sp - Scorzoni, L. [UNESP]; Benaducci, T. [UNESP]; Almeida, A. M F [UNESP]; Silva, Dulce Helena Siqueira [UNESP]; Bolzani, Vanderlan da Silva [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (My University, 2007)
Antifungal activity of natural products has been tested by adapting methods designed for synthetic drugs. In this study, two methods for the determination of antifungal activity of natural products, agar diffusion and broth microdilution, the CLSI reference methods for synthetic drugs, are compared and discussed. The microdilution method was more sensitive. The minimal inhibitory concentrations (MIC) of crude extracts, fractions and pure substances from different species of the plant families Piperaceae, Rubiaceae, Clusiaceae, Fabaceae and Lauraceae, from the Biota project, were determined. Antifungal activities against Candida albicans, C.krusei, C.parapsilosis and Cryptococcus neoformans were produced by several samples.
Keywords: Antifungal activity; Candida sp; Cryptococcus sp; Natural products; antifungal agent; clusiaceae extract; fabaceae extract; lauraceae extract; piperaceae extract; plant extract; rubiaceae extract; unclassified drug; angiosperm; antibiotic sensitivity; antifungal activity; broth dilution; Candida albicans; Candida krusei; Candida parapsilosis; comparative study; Cryptococcus neoformans; disk diffusion; drug activity; drug determination; drug screening; Guttiferae; legume; minimum inhibitory concentration; nonhuman; Piperaceae; Rubiaceae; sensitivity and sensibility; yeast